MISWAK (Salvadora persica) as a Cleansing Teeth - Mahanani, Erlina Sih; Samuel, Samantha Victoria (Universitas Muhammadiyah Yogyakarta, 2007)
Miswak is a chewing stick that derives from Arak tree (Salvadora persica) which is used as cleansing teeth. It is used in different part of Africa, Asia especially in Middle East, South of America,2 India, Pakistan and mostly of Muslim community. This custom was adopted and Islamized by Prophet Muhammad (Peace and Blessings of Allah be upon Him/PBUH) because there are several hadith mentioning the benefits of siwak in maintaining oral hygiene. Many studies have been done to explore the oral hygiene advantages of this stick. Salvadora persica contains trimethylamine, salvadorine, chloride, fluoride, silica, sulphur, mustard oil, vitamin C, resins and traces of tannins, saponins, flavonoids and sterol. Actually this chemical composition influence to the oral hygiene. The unique chemicals component, fibers proved the effect to periodontal status, caries, antimicrobial, cleanness, whitening, calculus removal, and so on. Furthermore miswak is generally used for a longer period of time and frequency (because it is used at least 5 times a day before praying). So normally the miswak users have higher oral hygiene status.